The Effectiveness of Fun Learning Approach in Arabic Learning - Bustam, Betty Mauli Rosa; Iswanto, Iswanto; Arqam, Mhd. Lailan; Juliani, Wikanti Iffah; Khairi, Akhmad Najibul (Universitas Islam Negeri Raden Intan Lampung, 2021)
Learning Arabic is often a burden for students, not only because the difficulty of its materials, but also the methods used by the teachers are often not attractive to students. This study aimed to develop Arabic learning materials for first grade in elementary school that will be based on fun learning approach. The method used in this research was Classic Experimental Design by dividing two classes in which one of the classes was utilized as a control class, and others were as experimental class (both 29 students), which would receive an experiment from the development of previous learning materials. The research result showed that the experimental class obtained an average difference score was about 27,2 with the highest score was 100, while the control class was about 10,3 with the highest score was 80. This study showed that there was a significant improvement in the test results of students in the experimental class, these results indicate that the use of textbook based on the song was more effective for students in Arabic learning. According to the results of this study and several other studies related to learning methods for the first graders in elementary school, this article provides an alternative learning method for Arabic teachers which has proven its effectiveness in delivering material. It is hoped that teachers can innovate to replace learning methods with fun learning which is more attractive to students.